Use of social media for the improvement of safety knowledge and awareness among Saudi Arabian phlebotomists - Attar, Razaz; Almohanna, Asmaa; Almusharraf, Ahlam; Alhazmi, Amal; Alanzi, Nouf; Al-Anezi, Fahad; Alanzi, Turki; Sroor, Raghad; Albishri, Ahmed; Alzahrani, Amwaj; Alsabilah, Taif; Alkenani, Ali; et al. (Frontiers in Medicine, 2023)
Purpose: The purpose of this study is to investigate the use of social media for the improvement of safety knowledge and awareness among phlebotomists Methods: As this study is intended to arrive at specific conclusions using empirical evidence, a deductive quantitative cross-sectional online survey design was adopted in this study. A total of 521 phlebotomists participated in the survey, and 86 incomplete responders were removed, resulting in a final sample of 435 considered in this study. T-tests and ANOVA were used to analyse the data.Results: A total of 41.6% stated that social media very effective, 31.5% stated that it was somewhat effective in improving safety knowledge and awareness. In addition, revealed no major differences between male and female participants (p> .05) with respect to the effectiveness of social media. However, statistically significant differences (p< .05) among the age groups were identified in relation to effectiveness of social media and intention to use in future.Conclusion: Social media applications are effective for knowledge dissemination among healthcare professionals.